CYCLICAL NATURE OF THE COAL MINING INDUSTRY IN UKRAINE AND ITS SUSTAINABLE DEVELOPMENT CAPACITY - Horoshkova, L.; Khlobystov, Y.; Volkov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The mechanism for Ukrainian coal mining industry's sustainable development management has been formed as a result of the study. Significant losses in the process of coal mining are proved to be one of the coal mining industry problems. It has been specified that the reserve for the industry's efficiency upgrading in the framework of more resource-saving behaviour is funding of mines reconstruction. Slowdown in the coal mining industry development has been determined to be the result of military operation in Donets'k and Luhans'k regions. The inefficiency of transport logistics for coal resources imported by Ukraine has been proved, since the rail freight transport is favored instead of cheaper maritime transport due to the underdeveloped quality of port infrastructure. Balancing mining, production of coal raw materials and their subsequent use in the production processes have been proved to be the ways to ensure rational use of coal resources of Ukraine. The processes for coking coal is metal production, and for anthracite – thermal energy production. Relationship between growth rates of coking coal mining and production, coke mining, exports and imports of coke and ironmaking during 2008– 2017s have been studied. It has been demonstrated that imports of coking coal essentially depends on the market pricing and has little to do with the needs of the metallurgical industry of Ukraine. It has been shown that the system for rational use of coking coal's capacity in Ukraine should include balancing flows of coal mining, coke and semi-coke mining according to the needs of national metallurgical industry, taking into account cyclical nature of its development. The necessity of coordinating the volumes of anthracite extraction, production and consumption and taking into account short cycles of heat power development have been defined.
Keywords: mineral and raw materials base; fuel and energy resources; hard coal; coking coal; anthracite; forecasting; modeling; management